Genetic diversity and evolution of enterovirus A71 subgenogroup C1 from children with hand, foot, and mouth disease in Thailand - Jiratchaya Puenpa (2022)
Enterovirus A71 (EV-A71) can cause hand, foot, and mouth disease (HFMD) in children and may be associated with severe neurological complications. There have been numerous reports of increased incidence of EV-A71 subgenogroup C1 (EV-A71 C1) infections associated with neurological diseases since the first occurrence in Germany in 2015. Here, we describe 11 full-length genome sequences of 2019 EV-A71 C1 strains isolated from HFMD patients in Thailand from 2019 to early 2020. The genetic evolution of 2019 EV-A71 C1 was traced in the outbreaks, and the emergence of multiple lineages was detected. Our results demonstrated that 2019 EV-A71 C1 from Thailand emerged through recombination between its nonstructural protein gene and those of other EV-A genotypes. Bayesian-based phylogenetic analysis showed that the 2019 EV-A71 C1 Thai strains share a common ancestor with variants in Europe (Denmark and France). The substitution rate for the 2019 EV-A71 C1 genome was estimated to be 4.38 × 10−3 substitutions/(site∙year−1) (95% highest posterior density interval: 3.84–4.94 × 10−3 substitutions/[site∙year−1]), approximating that observed between previous EV-A71 C1 outbreaks. These data are essential for understanding the evolution of EV-A C1 during the ongoing HFMD outbreak and may be relevant to disease outcomes in children worldwide.